FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN PENYAKIT SKABIES PADA SANTRI DI PONDOK PESANTREN QOTRUN NADA CIPAYUNG DEPOK FEBRUARI TAHUN 2016 - Hasna Ibadurrahmi; Silvia Veronica; Nunuk Nugrohowati (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Scabies is a skin disease caused by mite infestation and sensitization Sarcoptes scabiei variety hominis. Every student who live in dormitories boarding school has the same opportunities for the occurrence of scabies. Students and environmental characteristics of the rooms thought to contribute to the incidence of scabies. Tis study aims to determine what factors most inﬂuence on the incidence of scabies disease at boarding Qotrun Nada Cipayung Depok academic year 2015/2016. Tis research was observational analytic with cross sectional design. The subjects were 258 students of MTs and MA Boarding school of Qotrun Nada academic year 2015/2016. Data analysis was based on the incidence of disease scabies using Chi-square test (p < 0,05) and followed by multivariate logistic regression. Chi-Square test results showed that there was inﬂuence among knowledge, attitudes, student behavior, density of occupant, humidity, lighting, temperature, and room ventilation students with the incidence of scabies disease at boarding Qotrun Nada Cipayung, Depok. Results of multivariate logistic regression analysis showed the most inﬂuences characteristics were student attitude and density of occupant.